TAROMPA ODYSSEY: MEDIA ETNOMATEMATIKA SEBAGAI UPAYA MENINGKATKAN COLLABORATIVE CRITICAL THINKING SKILLS USIA PRA-REMAJA BERBASIS REALITAS TERTAMBA - Astika Sari; Andi Muhammad Irfan Taufan Asfar; Andi Muhamad Iqbal Akbar Asfar; Andi Nurannisa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The main problems in this study are: How to develop Tarompa Odyssey media to improve Collaborative Critical thinking of pre-adolescent students that is valid, practical, and effective. How is the effect of Tarompa Odyssey learning media on Collaborative Critical thinking of pre-adolescent students, and How are students' perceptions of the use of Tarompa Odyssey media in mathematics learning. This study aims to determine the development of Tarompa Odyssey media to improve the Collaborative Critical thinking of pre-adolescent students that is valid, practical, and effective. And to determine the effect of Tarompa Odyssey learning media on Collaborative Critical thinking of pre-adolescent students and to determine students' perceptions of the use of Tarompa Odyssey media in mathematics learning. This type of research is development research, R&D (Research and Development). The research procedure includes research preparation, literature search, and research process. The subjects in this study were students of class VIII A as the experimental class and VIII B as the control class, with a total of 60 students. The research results show that the practicality level is very high, proven by a percentage of 94.25% for students and 93% for teachers. The media is effective in improving Collaborative Critical thinking of students, with a significant difference between the Pre-test and Post-test results (p < 0.05). In addition, students' perceptions of this media are very positive, with an average of 75% positive answers. Thus, the Tarompa Odyssey learning media is a valid, practical, and effective innovation in improving students' and collaborative thinking skills.